Detection of Mycobacterium tuberculosis lipoarabinomannan and CFP-10 (Rv3874) from urinary extracellular vesicles of tuberculosis patients by immuno-PCR. Issue 5 (7th September 2019) - Dahiya, Bhawna; Khan, Anish; Mor, Preeti; Kamra, Ekta; Singh, Netrapal; Gupta, Krishna B; Sheoran, Abhishek; Sreenivas, Vishnubhatla; Mehta, Promod K
ABSTRACT: Extracellular vesicles (EVs), the small circulating vesicles released from urine samples of tuberculosis (TB) patients, contain a pool of biomarkers. We recently detected Mycobacterium tuberculosis lipoarabinomannan (LAM) and CFP-10 (Rv3874) biomarkers from the urinary EVs of pulmonary TB (PTB) and extrapulmonary TB (EPTB) patients by immuno-polymerase chain reaction (I-PCR) assay and the results were compared with the analogous enzyme-linked immunosorbent assay (ELISA). The detection limits of both purified LAM and CFP-10 were determined to be 1 fg/mL with I-PCR, which was 10 6 times lower than ELISA. Detection of LAM and CFP-10 biomarkers in urinary EVs of TB patients by I-PCR showed superiority over ELISA. Notably, LAM I-PCR revealed sensitivities of 74.3 and 67.9% in PTB ( n  = 74) and EPTB ( n  = 53) patients, respectively, with specificities of 91.5–92.8% ( n  = 116). Moreover, the sensitivities attained with LAM I-PCR were significantly higher ( P  < 0.01) than with CFP-10 I-PCR. After further improving the sensitivity and specificity of the assay, our I-PCR based on LAM detection in urinary EVs may be used as an adjunct test for rapid diagnosis of TB. Abstract : Immuno-PCR assay was employed for the detection of mycobacterial lipoarabinomannan in urinary extracellular vesicles of pulmonary and extrapulmonary tuberculosis patients, and showed superiority over CFP-10 detection.